PERBANDINGAN PARTIKEL DE çš„ BAHASA MANDARIN DENGAN KATA BERFUNGSI SAMA DALAM BAHASA INDONESIA - Junaeny, Arini (Universitas Negeri Makassar, 2020)
Abstract. Mandarin is one of the most widely used languages in the world. During the learning process, mother language sometimes influences second language learning. Therefore it is necessary to compare the rules of linguistic or comparative linguistics. This study uses a qualitative description method. The word